Impact of thyroid-stimulating hormone levels after controlled ovarian hyperstimulation on in vitro fertilization/intracytoplasmic sperm injection outcomes in women with fresh embryo transfer: a prospective cohort study - Huang, Ning; Chen, Lixue; Lian, Ying; Chi, Hongbin; Qiao, Jie (Frontiers in Endocrinology, 2023)
Objective: Maternal hypothyroidism before and during pregnancy is associated with an increased risk of adverse pregnancy outcomes; many studies have evidenced that controlled ovarian hyperstimulation (COH) triggers a significant increase in the levels of TSH; however, no large-scale prospective studies have evaluated the impact of TSH levels after COH on assisted reproductive technology outcomes. The aim of this prospective study was to investigate whether in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) outcomes are affected by TSH levels after COH in women with fresh embryo transfer (ET).Methods: A total of 664 patients who underwent IVF/ICSI treatment and received fresh ET at the Peking University Third Hospital were included in this study. The rates of clinical pregnancy, miscarriage, live birth, and preterm delivery were analyzed.The patients were categorized into two groups based on serum TSH levels after COH (0.55 mIU/L < TSH < 2.5 mIU/L: n= 449, 2.5 mIU/L ≤ TSH ≤ 4.78 mIU/L: n= 215). There were no significant differences in the rates of clinical pregnancy, miscarriage, and live birth between the two groups, even after adjusting for age, body mass index (BMI), thyroid antibody positivity, and COH protocols. However, the preterm delivery rate was significantly higher in women with TSH < 2.5 mIU/L than in those with TSH ≥ 2.5 mIU/L, even after adjusting for relevant confounding factors.There was no significant difference in live birth weight between the two groups.